2020
DOI: 10.1055/s-0040-1707326
|View full text |Cite
|
Sign up to set email alerts
|

Designing the Secondary Coordination Sphere in Small-Molecule Catalysis

Abstract: The application of secondary-sphere interactions in catalysis was inspired by the hierarchical arrangement of the microenvironment of metalloprotein active sites and has been adopted mainly in organometallic catalysis. The study of such interactions has enabled the deliberate orientation of reaction components, leading to control over reactivity and selectivity by design. Although not as common, such interaction can play a decisive role in organocatalysis. Herein, we present several examples of small-molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…192−194 In 2019, we reported that the catalytic activity of N-heterocyclic carbene (NHC) triazolium salts bearing a hydroxy handle could be fine tuned by the in situ addition of boronic acids as second-sphere modifiers. 194,195 This strategy also enabled more rapid data collection because the catalyst structure was modified without the need to synthesize libraries of catalysts. In this work, we investigated the effect of second-sphere modifications on benzoin reactions with a focus on electron-deficient aldehydes, which were notoriously challenging because of facile racemization.…”
Section: ■ Enhanced Data Visualizationmentioning
confidence: 99%
“…192−194 In 2019, we reported that the catalytic activity of N-heterocyclic carbene (NHC) triazolium salts bearing a hydroxy handle could be fine tuned by the in situ addition of boronic acids as second-sphere modifiers. 194,195 This strategy also enabled more rapid data collection because the catalyst structure was modified without the need to synthesize libraries of catalysts. In this work, we investigated the effect of second-sphere modifications on benzoin reactions with a focus on electron-deficient aldehydes, which were notoriously challenging because of facile racemization.…”
Section: ■ Enhanced Data Visualizationmentioning
confidence: 99%
“…As part of our ongoing program on secondary sphere modified organocatalysts, 18 we recently reported the application of amino catalysts in an aldol reaction between aromatic aldehydes and cyclopentanone ( Figure 2 .a). 19 By modifying proline with boronic acids in situ we were able to rapidly access different organocatalyst derivatives without any synthetic effort.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular recognition may represent a versatile tool to overcome the synthetic challenges of tuning the second coordination sphere of a catalyst,[ 5j , 15 , 16 ] and test the validity of this approach (Figure 1 C). In particular, catalysts CR M and CR,X M (Figure 2 , M=Fe, Mn) bearing two or one 18‐benzo‐crown‐6‐ether (CR) receptors, respectively, strongly bind protonated primary amines, promoting their selective C−H oxidation.…”
Section: Introductionmentioning
confidence: 99%